Efecto de las ventanas de nacimiento en la respuesta inmunológica de pollos COBB 500 de ambos sexos - Pinto Tobar, Jeorgette Jessica (2023)
The effect of hatching windows on the immune response of COBB 500 chickens of both sexes was evaluated. 480 chicks were used, 40 chicks for each birth window, 20 females and 20 males. A completely randomized block design was proposed, with eight treatments, from T1 to T4 males born at 486, 492, 498 and 504 hours, T5 to T8 females with the same hours. The variables maternal and vaccine antibodies, chick weight, lymphoid organ weight and morphometry were evaluated. The results show that the maternal and vaccine antibody titers did not have significant differences (P<0.05), with respect to the hours of birth and sex. In the weight and morphometry of lymphoid organs, no significant differences (P<0.05) were found on the day of birth, except in chick weights, the weight of the yolk sac was higher in females, the morphometry of Fabricio's bag was different among males. treatments; on day 21, significant differences were found for all the variables, however, with respect to sex, there are no differences in weight and diameter of the bursa of Fabricio and spleen morphometry. It is concluded that the birth windows and sex do not affect the antibody levels in chickens on day 21 and day of birth, nor on the weight and morphometry of lymphoid organs on day 21, but on day 21 an effect is shown on these variables.